Propranolol Attenuates Late Sodium Current in a Long QT Syndrome Type 3-Human Induced Pluripotent Stem Cell Model - Hirose, Sayako; Makiyama, Takeru; Melgari, Dario; Yamamoto, Yuta; Wuriyanghai, Yimin; Yokoi, Fumika; Nishiuchi, Suguru; Harita, Takeshi; Hayano, Mamoru; Kohjitani, Hirohiko; Gao, Jingshan; Kashiwa, Asami; et al. (Frontiers in Cell and Developmental Biology, 2020)
Background: Long QT syndrome type 3 (LQT3) is caused by gain-of-function mutations in the SCN5A gene, which encodes the α subunit of the cardiac voltage-gated sodium channel. LQT3 patients present bradycardia and lethal arrhythmias during rest or sleep. Further, the efficacy of β-blockers, the drug used for their treatment, is uncertain. Recently, a large multicenter LQT3 cohort study demonstrated that β-blocker therapy reduced the risk of life-threatening cardiac events in female patients; however, the detailed mechanism of action remains unclear. Objectives: This study aimed to establish LQT3-human induced pluripotent stem cells (hiPSCs) and to investigate the effect of propranolol in this model. Method: An hiPSCs cell line was established from peripheral blood mononuclear cells of a boy with LQT3 carrying the SCN5A-N1774D mutation. He had suffered from repetitive torsades de pointes with QT prolongation since birth (QTc 680 ms), which were effectively treated with propranolol, as it suppressed lethal arrhythmias. Furthermore, hiPSCs were differentiated into cardiomyocytes (CMs), on which electrophysiological functional assays were performed using the patch-clamp method. Results: N1774D-hiPSC-CMs exhibited significantly prolonged action potential durations (APDs) in comparison to those of the control cells (N1774D: 440 ± 37 ms vs. control: 272 ± 22 ms; at 1 Hz pacing; p < 0.01). Furthermore, N1774D-hiPSC-CMs presented gain-of-function features: a hyperpolarized shift of steady-state activation and increased late sodium current compared to those of the control cells. 5 μM propranolol shortened APDs and inhibited late sodium current in N1774D-hiPSC-CMs, but did not significantly affect in the control cells. In addition, even in the presence of intrapipette GDPβs, an inhibitor of G proteins, propranolol reduced late sodium current in N1774D cells. Therefore, these results suggested a unique inhibitory effect of propranolol on late sodium current unrelated to β-adrenergic receptor block in N1774D-hiPSC-CMs. Conclusion: We successfully recapitulated the clinical phenotype of LQT3 using patient-derived hiPSC-CMs and determined that the mechanism, by which propranolol inhibited the late sodium current, was independent of β-adrenergic receptor signaling pathway.